PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA BAGI PETUGAS KEBERSIHAN DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN BADUNG - Dewi, I Gusti Agung Ayu Kade Ita Puspita; Putra, Made Aditya Pramana (Kertha Negara : Journal Ilmu Hukum, 2024)
The purpose of this research is to determine the implementation of occupational health and safety protection and the measures taken to reduce hazards and prevent work accidents and work-related illnesses among sanitation workers in the Environmental and Sanitation Agency of Badung Regency. The research methodology employed in this study is empirical legal research, utilizing a case and factual approach as its foundation. The research findings indicate that occupational health and safety protection for sanitation workers in the Environmental and Sanitation Agency of Badung Regency adheres to the applicable legal regulations. However, it is observed that some sanitation workers choose not to utilize the provided safety equipment while carrying out their duties. Furthermore, the absence of the implementation of occupational health and safety management system (SMK3) and the establishment of the Occupational Health and Safety Committee (P2K3) has resulted in inadequate efforts to control the risks of hazards undertaken by the Environmental and Sanitation Agency of Badung Regency, thus failing to effectively reduce work accidents and work-related illnesses.